129k views
2 votes
Change of subject x the subject
y=2x+3/5x-2

User Amir Amir
by
4.9k points

1 Answer

3 votes

Answer:

x =
(3+2y)/(5y-2)

Explanation:

Given

y =
(2x+3)/(5x-2) ← multiply both sides by (5x - 2)

y(5x - 2) = 2x + 3 ← distribute left side

5xy - 2y = 2x + 3 ( add 2y to both sides )

5xy = 2x + 3 + 2y ( subtract 2x from both sides )

5xy - 2x = 3 + 2y ( factor out x from each term on the left side )

x(5y - 2) = 3 + 2y ← divide both sides by (5y - 2)

x =
(3+2y)/(5y-2)

User Cyroxis
by
6.3k points